A contribution to the investigation of the heat load of shock absorbers of semi-active suspensions in motor vehicles - Demić, Miroslav D. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Dynamic simulation, based on modeling, has a significant role during the process of vehicle development. It is especially important in the first stages of vehicle design, when relevant vehicle parameters are to be defined. Shock absorbers as executive parts of vehicle semi-active suspension systems suffer thermal loads, which may result in damage and degradation of ther characteristics. Therefore,this paper shows an attempt to analyze converting of mechanical work into heat by using the dynamic simulation method. Introduction Shock absorbers are integral elements of semi-active suspension systems for vehicles (hereinafter SASS). They directly affect the active vehicle safety. The role of shock absorbers is to absorb mechanical vibrations transferred from the road and to ensure the safety of passengers in a vehicle. The kinetic energy of vehicle vibrations transforms into mechanical work or heat in shock absorbers. In practice, in the first stage of vehicle development, the shock absorber parameters are chosen from the condition of damping vibrations of vehicles, but their thermal shock loads should be also taken into account. Motor vehicles have complex dynamic characteristics manifested by spatial movement, parameters change during operation, a number of disturbing influences, backlash, friction, hysteresis, etc. The above-mentioned dynamic phenomena, especially vibration, lead to fatigue of driver and users, reduce the life of the vehicle and its systems, etc. The main objective of the system is to reduce the reliance of the above-mentioned negative effects, improving the vehicle behavior on the road and allow the exploitation of vehicles in a wide range of service conditions. Classical systems cannot satisfiy these conditions, so there was a need to introduce new suspension systems with controlled characteristics (briefly called "semi-active", or "active" systems). Oscillatory model of vehicle The differential equations of vibratory motion of the given vehicle model have been written using the "NEWEUL." software package. The data input has been done in accordance with the program requirements, and 24 coordinate systems (including inertial-OI1I2I3 global coordinate system) have been used to define the dynamic vehicle model with seven degrees of freedom. Thermal load on the shock absorbers of the semi-active suspension system Due to the relative motion between sprunged and unsprunged masses, mechanical work in the absorbers is equivalent to the amount of heat Q, J. As the heat flux is of a random size, it was assessed as appropriate to calculate the average power (flux) for each buffer separately, and the data are given in Table 1 Table 1 Medium heat flux during a movement of 20, s Medium flux, W Front left absorber Front right absorber Rear left absorber Rear right absorber Speed 30,m/s, Mass 100% 2.330434E-006 5.569178E-006 5.358273E-006 2.944404E-006 Speed 5, m/s Mass 100% 2.435122E-006 5.673833E-006 5.477176E-006 2.968751E-006 Mass 75%, Speed 5, m/s 2.431798E-006 4.518553E-006 4.263119E-006 2.748116E-006 For illustration, Fig. 1 shows the work converted to heat amount in the shock absorbers of the semi-active suspension system, for a vehicle speed of 5 m/s. The analysis of the heat amount data for a speed of 5 and 30, m/s,for an illustrative example of a speed of 5, m / s , given in Fig. 1 shows that the amount of heat production increases with the covered distance (time). If the vehicle speed increases, the amount of heat decreases. The example in Fig. 2 shows the effect of the vehicle load on the heat amount generated in the semi-active suspension system absorbers. Namely, the figure shows mechanical work (converted into heat) in the shock absorbers of a partially loaded vehicle (75%) while moving at a speed of 5, m / s. It can be determined that the reduced load on a vehicle leads to reduced thermal shock loading of vehicles, which is in accordance with heat flux. Conclusion Based on the study,the following can be concluded: • Models of vehicles with semi-active suspension systems can be used for calculating thermal load on the suspension, • speed increase during vehicle movement along the path of identical properties, decreases the production of heat in shock absorbers, and • increase in load of the vehicle leads to the increase in the production of heat in shock absorbers.